RELATIONSHIP OF MOTHER KNOWLEDGE ABOUT EDUCATIONAL TOYS WITH DEVELOPMENT OF PRESCHOOL CHILDREN IN THE VILLAGE OF JOMBOR CEPER KLATEN - Erlina Hermawati; Sumantri .; Feri Catur Yuliani (STIKES DUTAGAMA KLATEN, 2012)
Background: The preschool children who is entering a period of play, so there are needs of a game. The game takes the child can hone the child's development in accordance with their stage of growth and development. Educational toys are toys that can optimize the child's development. Objectives: The purpose of this study was to determine of correlation betwen mother of knowledge about educational toys with development of preschool children in the Village of Jombor Ceper Klaten. Methods: This study was analytical observational method with cross sectional approach. The population in this study were mother who have preschool children and preschool children in the Village of Jombor Ceper Klaten as much as 64 mothers and 67 children. The sampling techniques used in the study was purposive sampling with decide the inclusion criteria. The data analysis conducted by correlation analysis and to seek relationships between the two variable used Spearman rank correlation analysis. Results: There was a significant relationship between mother knowledge about educational toys with the development of preschool children in the village of Jombor Ceper Klaten, with a value of ρ = 0.001 (ρ <0.05), t count = 3.396 (t count > t table) and the value of r =0 .433. The results of this study can be concluded that the mother’s knowledge about educational toys was good, so the development of preschool children will be normal, so the hypothesis in this study was received. Conclusion: The mother’s knowledge about educational toys was good, so the development of preschool children will be normal.